PERANAN ROOM ATTENDANT DALAM MENINGKATKAN PELAYANAN UNTUK KEPUASAN TAMU DI REDTOP HOTEL AND CONVENTION CENTER - Chandrasari, Ati; Eko, Obi; Givan, Bryan (LPPM Universitas Nusa Mandiri, 2023)
In this Jurnal the author conducted research on REDTOP Hotel And Convention Center in Jakarta in the Housekeeping Department. REDTOP Hotel and Convention Center is a four-star hotel right in the Center of Jakarta area. Understanding Room Attendant to SOP (Standard Operating Procedure) which applies to the perceived level of guest statisfaction during the stay, it is intended that the quality of existing services in REDTOP Hotel and Convention Center for the better in the eyes of the guest who come This research was conducted to determine the strategic role of room attendance in increasing customer satisfaction and room occupancy rates from January to March. The results were obtained through the method of data collection and observation with the service provided in accordance with applicable regulations. The results obtained are an increase in service satisfaction of Room Antendant by 76% from January to February and an increase in service satisfaction of 84% from February to March at the Red Top Hotel and Convention center Of both methods are expected to answer the fundamental problems of research : “The role of the room attendant improves the quality of service for the guest statisfaction at Red Top Hotel and Convention Centre.”